Implementasi visi Ilmu Amaliyah, Amal Ilmiyah, dan Akhlaqul Karimah untuk meningkatkan pemahaman siswa pada mata pelajaran Akidah Akhlak kelas X di MA Al-Amin boarding school Sooko Mojokerto - Afif, Muthoharun (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
As is commonly understood, pesantren has historically ordained its existence as an educational institution that emphasizes the so-called akhlaqul karimah, a term commensurate with the term character. This is because the process of learning and education in pesantren not only emphasizes cognitive intelligence, but also affective and psychomotor. And exactly that is the spirit and ideals of the founding of Al-Amin Islamic Boarding School, with his vision of Amaliyah, Amal Ilmiyah, and Akhlaqul Karimah, based on the Islamic teachings of Ahlus Sunnah Wal Jama'ah. The purpose of this research is: To describe Implementation of vision of Amaliyah, Amal Ilmiyah, and Akhlaqul Karimah, teacher activity in learning with vision of Amaliyah, Amal Ilmiyah and Akhlaqul Karimah, student activity in learning by using vision of Amaliyah, Amal Ilmiyah and Akhlaqul Karimahdan student response in learning by using the vision of Science Amaliyah, Amal Ilmiyah, and Akhlaqul Karimah to improve students' understanding on the subject Akidah Akhlak class X in MA Al-Amin boarding school Sooko Mojokerto. This development research was conducted in the even semester of the academic year 2016/2017. The approach used in this study is a qualitative approach, that is descriptive and without using statistical analysis. The action is carried out according to the model proposed by Tripp consisting of 4 stages: (1) planning (plan): Action planning and research planning (Plan Research), (2) acts: (action), (3) research: produce data and analyze data, and reflection. The results of this research are: 1) Implementation of vision of Amaliyah, Amal Ilmiyah, and Akhlaqul Karimah in class X in MA Al-Amin boarding school Sooko Mojokerto can increase class enthusiasm. 2) The accumulated results of teacher activity can improve students' understanding on the subjects of Akidah Akhlak class X in MA Al-Amin boarding school Sooko Mojokerto very well. 3) The result of accumulation of student activity observed is quite enthusiastic. 4) Implementation of the vision of Amaliyah, Amal Ilmiyah, and Akhlaqul Karimah can improve students' understanding on the subjects of Akidah Akhlak class X in MA Al-Amin boarding school Sooko Mojokerto.